Attitudes and Perceptions of Canadian Otolaryngology‐Head and Neck Surgeons and Residents on Environmental Sustainability. Issue 1 (23rd February 2023) - Hathi, Kalpesh; Fowler, James; Zahabi, Sarah; Dzioba, Agnieszka; Madou, Edward; Gunz, Anna C.; Sowerby, Leigh J.; Nichols, Anthony C.; Strychowsky, Julie E.
Abstract: Objective: Healthcare systems, specifically operating rooms, significantly contribute to greenhouse gas emissions. Addressing operating room environmental sustainability requires understanding current practices, opinions, and barriers. This is the first study assessing the attitudes and perceptions of otolaryngologists on environmental sustainability. Study Design: Cross‐sectional virtual survey. Setting: Email survey to active members of the Canadian Society of Otolaryngology–Head and Neck Surgery. Methods: A 23‐question survey was developed in REDCap. The questions focused on four themes: (1) demographics, (2) attitudes and beliefs, (3) institutional practices, and (4) education. A combination of multiple choice, Likert‐scale, and open‐ended questions were employed. Results: Response rate was 11% (n = 80/699). Most respondents strongly believed in climate change (86%). Only 20% strongly agree that operating rooms contribute to the climate crisis. Most agree environmental sustainability is very important at home (62%) and in their community (64%), only 46% said it was very important in the operating room. Barriers to environmental sustainability were incentives (68%), hospital supports (60%), information/knowledge (59%), cost (58%), and time (50%). Of those involved in residency programs, 89% (n = 49/55) reported there was no education on environmental sustainability or they were unsure if there was. Conclusion: Canadian otolaryngologists strongly believe in climate change, but there is more ambivalence regarding operating rooms as a significant contributor. There is a need for further education and a systemic reduction of barriers to facilitate eco‐action in otolaryngology operating rooms.